(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Eugenia jambolana is common plant which is mainly found in Indian sub continents. Jamun is Indian name of this plant. It has various pharmacological properties like antiviral, antidiabetic, antioxidants etc. In the present review we have highlighted the various pharmacological properties of Eugenia Jambolana with different chemical structures. Different extracts of Eugenia jambolana have been highlighted.